2016
DOI: 10.1007/s11852-016-0438-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reclamation on heavy metal pollution in a coastal wetland reserve

Abstract: Owing to accelerating reclamation activities in the coastal wetland reserves, it is of great importance to analyze the effects of wetland reclamation on heavy metal pollution in these areas. Soil samples were collected from reclamation and natural habitats in Yancheng National Nature Reserve for Coastal Rare Birds in Jiangsu, China to investigate the effects of reclamation on the total amounts, availability, and vertical distribution of seven elemental heavy-metal pollutants. In general, the total amount and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Compared with the Chinese Soil Environmental Quality Standard (GB 15618-1995), the average concentrations of PHEs were all within the range. In general, the concentrations of PHEs in the tidal flat reclamation area were relatively low, which is similar to the conclusions of other researches in Jiangsu coastal areas, and might be related to the local geochemical background [45,46]. Lv et al [47] demonstrated that the background concentrations of Cr, Cu, Ni, Pb, and Zn in marine sediments were significantly lower than that in river alluvial deposits, lagoonal facie sediments, and delta sediments.…”
Section: Descriptive Analysissupporting
confidence: 81%
“…Compared with the Chinese Soil Environmental Quality Standard (GB 15618-1995), the average concentrations of PHEs were all within the range. In general, the concentrations of PHEs in the tidal flat reclamation area were relatively low, which is similar to the conclusions of other researches in Jiangsu coastal areas, and might be related to the local geochemical background [45,46]. Lv et al [47] demonstrated that the background concentrations of Cr, Cu, Ni, Pb, and Zn in marine sediments were significantly lower than that in river alluvial deposits, lagoonal facie sediments, and delta sediments.…”
Section: Descriptive Analysissupporting
confidence: 81%
“…Thus, the nature reserve has been subject to disturbance from industry (Wang et al 2010), agriculture (Li et al 2014), and aquaculture (Zuo et al 2004), both locally and in adjacent areas, and native wetland vegetation is being extensively converted for urbanization, farming, or aquaculture (Shi et al 2017). Conflicts between ecological protection and economic development have thus become increasingly prominent (Lu et al 2007;Xu et al 2016aXu et al , 2016b.…”
Section: Study Area and Study Objectmentioning
confidence: 99%
“…The Anthropocene has been proposed as a new geo-stratigraphic epoch in which humans have become a global factor affecting ecosystems (Biermann et al 2016). To further separate the respective contributions of human activity and natural factors to changes in landscape patterns based on previous studies (Walz and Stein 2014;Xu et al 2016aXu et al , 2016b, we constructed a qualitatively and quantitatively integrated HDI model:…”
Section: Human Disturbance Index (Hdi)mentioning
confidence: 99%
See 1 more Smart Citation
“…On a global scale, the loss of wetlands has been estimated at 50% since 1900 [ 3 ]. In some locations, reclaimed wetlands have provided productive agriculture, economic or greenhouse gas mitigation benefits [ 4 6 ], but in other areas this has resulted in a negative net outcome to ecosystem services or a direct environmental collapse [ 7 9 ]. The ecosystem loss from landscape reclamation has also significantly impacted habitat for aquatic and terrestrial fauna, including internationally protected migratory wader birds [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%